Heated, Humidified High-Flow Nasal Cannulae as a Form of Noninvasive Respiratory Support for Preterm Infants and Children with Acute Respiratory Failure - Mardegan, Veronica; Priante, Elena; Lolli, Elisabetta; Lago, Paola; Baraldi, Eugenio (American Journal of Perinatology, 2016)
Heated, humidified high-flow delivered by nasal cannulae (HHHFNC) is increasingly used for noninvasive respiratory support in preterm infants and critically ill children due to its perceived effectiveness and ease of use. Evidence from randomized controlled trials suggests that HHHFNC and continuous positive airway pressure (CPAP) are equally effective as postextubation support in preterm infants. HHHFNC is also used for weaning preterm infants from CPAP. Data on HHHFNC used as the primary support for treating respiratory distress syndrome are conflicting. HHHFNC use in preterm infants is associated with reduced nasal trauma. Inability to measure the pressure generated by HHHFNC systems is a concern because overexpansion can lead to an air leak and lung injury. Great caution is warranted when HHHFNC is used in extremely low-birth-weight infants (who were rarely included in these randomized controlled trials) because a recent retrospective study found its use is associated with a higher likelihood of bronchopulmonary dysplasia or death in this population. HHHFNC has also become popular in pediatric intensive care units and pediatric wards as a method for delivering oxygen and noninvasive respiratory support. Most published studies were conducted on infants and young children with bronchiolitis. The results of a few observational studies and two randomized trials suggest that HHHFNC therapy is effective in the treatment of bronchiolitis. This review discusses the proposed mechanisms of action behind HHHFNC, the results of observational studies, and the evidence emerging from clinical trials on the use of HHHFNC in preterm infants and children critically ill with bronchiolitis.
Keywords: high-flow nasal cannulae; noninvasive respiratory support; infant/newborn; bronchiolitis